Gender Differences in Faculty Turnover - Byron W. Brown; Stephen A. Woodbury (W.E. Upjohn Institute for Employment Research, 1995)
Over the last 15 to 20 years, colleges and universities have paid increasing attention to attracting and retaining faculty women. The rate of progress of women in academe has nevertheless been painfully slow. For example, statistics on economists collected and published by the American Economic Association (Committee on the Status of Women in the Economics Profession 1994) suggest that in recent years, about 20 percent of Economics assistant professors in graduate Ph.D.-granting departments were women, about 10 percent of associate professors were women, and under 5 percent of full professors were women. The percentage of new assistant professors who are women has lagged behind the percentage of new Ph.D.s who are women by 10 to 15 percentage points. And the percentage of promotions to associate (and full) professor that are accounted for by women has lagged behind the percentage of assistant (and associate) professors who were women and "promotable." One of the explanations (or perhaps excuses) offered for the slow progress of women in academe is that faculty women have higher rates of voluntary turnover than do faculty men. This explanation accords with the general finding that women have higher rates of labor market turnover than do men (Blau and Kahn 1981; Light and Ureta 1992), and may provide a psychic calm both for those frustrated by the slow progress of women in academe and for those who might frustrate that progress. Studies to date of faculty turnover have used grouped (or university-level) data, which usually preclude examination of gender differences in faculty turnover (Ehrenberg, Kasper, and Rees 1991; Rees and Smith 1991). In this paper we offer evidence on faculty turnover using micro data from a single large public university Michigan State University (MSU) during the decade of the 1980s. Our findings suggest strongly that the higher separation rates that are observed for faculty women are accounted for by differences between men and women in appointment status that is, faculty women have higher turnover rates than faculty men because a higher percentage of women than of men hold temporary appointments.
Keywords: J0; J2; J6; 330; faculty; college; gender; turnover; Brown; Woodbury